Boswellic acids: privileged structures to develop lead compounds for anticancer drug discovery. (3rd August 2021) - Hussain, Hidayat; Ali, Iftikhar; Wang, Daijie; Hakkim, Faruck L.; Westermann, Bernhard; Rashan, Luay; Ahmed, Ishtiaq; Green, Ivan R.
ABSTRACT: Introduction : Cancer has been identified to be the second major cause of death internationally as exemplified by ca. 9.6 million deaths in 2018 along with ca. 18 million new patients in 2018 that have been recorded. Natural boswellic acids (BAs) and their source, frankincense, have been reported to possess in vitro and in vivo anticancer effects toward various cancer cells. Areas covered : This comprehensive review focuses on the importance of boswellic acids (BAs) for the establishment of future treatments of cancer. Moreover, potent semisynthetic derivatives of BAs have been described along with their mode of action. In addition, important structural features of the semisynthetic BAs required for cytotoxic effects are also discussed. Expert opinion : Numerous semisynthetic BAs illustrate excellent cytotoxic effects. Of note, compounds bearing cyanoenone moieties in ring A, endoperoxides and hybrids display increased and more potent cytotoxic effects compared with other semisynthetic BAs. Moreover, BAs have the potential to conjugate or couple with other anticancer compounds to synergistically increase their combined anticancer effects. In addition, to get derived BAs to become lead anticancer compounds, future research should focus on the preparation of ring A cyanoenones, endoperoxides, and C-24 amide analogs.